Separation and Preconcentration for Determination of Ultra Trace of Chromium(III) and Zinc(II) Using Spectrofluorimetry Techniques - H. Kadhim, Kasim; N. Alsharifi, Abbas; S. Abbas*, Ahmed (Asian Journal of Chemistry, 2014)
Cloud point extraction has been used for the preconcentration of ultra-trace amount of chromium and zinc, after the formation of a complex with doxycycline hyclate as a drug in a surfactant solution yielding a hydrophobic complex, which then is entrapped in surfactant micelles and further determination by spectrofluorimetry. The main factors affecting the determination, such as pH, concentration of reagent and surfactant, equilibration temperature and time on cloud point extraction, were optimized for the best extract efficiency. The calibration graph was linear in the range of (0.025-1) and (10-100) ng mL-1 with detection limit of (0.01, 7.8) ng mL-1. The proposed technique was applied to the determination of chromium(III) and zinc(II) in milk samples with satisfactory analytical results.